A Comparison of Student-Athlete and Non-Athletes Perceptions of Academic Advisement Services - Gillentine, Andy; Nix, Charlie; Hunt, Barry (My University, 2001)
The purpose of this study was to examine academic advisement expectations of student-athletes. Participants in this study included 189 graduate and undergraduate students enrolled in a variety of courses offered through the Health, Physical Education, Recreation, & Sport program at a large Southeastern University. Thirty-eight percent (N=71) of the participants identified themselves as collegiate athletes. The students completed a survey instrument addressing expectations of their academic advisor. Student-athletes surveyed in this study demonstrated advisement expectations similar to those of the general student population. Mean responses to survey items indicated non-athletes placed more importance on individual survey items than did the student-athletes. Advisor's knowledge of course offerings within the department was considered important by 92.5% of all students. These findings assisted in identifying specifc elements useful in improving the academic advisement process and meeting student expectations. Student-athletes surveyed in this study demonstrated advisement expectations similar to those of the general student population. The authors asked, "Given that the levels of importance were similar for both groups, is there a need for separate academic advisement for student-athletes" (p. 89)?
Keywords: academic support